2023
DOI: 10.1186/s13011-022-00513-y
|View full text |Cite
|
Sign up to set email alerts
|

Qualitative description of outreach and engagement in perinatal substance treatment in Finland

Abstract: Background Women with perinatal substance problems experience a multitude of barriers to care. They have specific early intervention needs, they endure societal stigma, and both substances and mental health issues influence the way they navigate within support and treatment systems. Early interventions for women with perinatal substance problems are underresearched contexts. The aim of the study is to describe building relationships and engagement within an outreach and low threshold service en… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 48 publications
0
3
0
Order By: Relevance
“…Recovery is on a continuum and is a personal journey that differs for everyone. Health providers must exercise an empathetic and non-judgmental approach to patient management and provision of care [52] . Recovery is achieved through certain basic principles:…”
Section: Benefits Of Harm Reduction Strategiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Recovery is on a continuum and is a personal journey that differs for everyone. Health providers must exercise an empathetic and non-judgmental approach to patient management and provision of care [52] . Recovery is achieved through certain basic principles:…”
Section: Benefits Of Harm Reduction Strategiesmentioning
confidence: 99%
“…Choice and empowerment are reliant on the provider's recognition of each women's dignity and autonomy. Providers must exercise humility and acknowledge that each woman understands her own social, mental, emotional, physical, spiritual, and cultural needs best [52,53] . Measures to preserve patient autonomy allow for collaborative decision -making and trusting relationships between patient and provider [51,53] .…”
Section: Maternal Choice and Empowermentmentioning
confidence: 99%
“…Other research has suggested that PPWUD prefer to access SRH services in spaces they already frequent, such as harm reduction programs, or through mobile outreach services [15,31,32]. Additional facilitators of access include strong social support networks, trusting relationships with medical providers, gender-specific services (e.g., counselling for gender-based violence), accessible transportation, no-cost services, walkin and virtual services, augmented program funding, and dedicated gender and addictions medical training [13,15,[32][33][34][35][36]. Nevertheless, programs and practices must also transcend the individual and interpersonal levels to address structural and rights-based barriers [37].…”
Section: Introductionmentioning
confidence: 99%